Pengaruh Sales Growth, Collateralizable Assets, Investment Opportunity Set, dan Managerial Ownership Terhadap Kebijakan Dividen Pada Perusahaan Sektor Consumer Non-Cyclicals Yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2023: Studi Empiris pada Perusahaan Consumer Non-Cyclicals di BEI Periode 2021–2023 - Mayang Sari; RA Sista Paramita (Jurnal Ilmu Manajemen, 2025)
This study investigates the impact of sales growth, collateralizable assets, investment opportunity set, and managerial ownership on dividend policy among consumer non-cyclical companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. Using a quantitative approach with panel data regression analysis in STATA version 17, the study analyzes secondary data obtained from 41 purposively selected companies. The findings reveal that the investment opportunity set, measured by the market-to-book value of equity (MBVE), exerts a positive and significant effect on dividend policy. In contrast, sales growth, collateralizable assets, and managerial ownership show no statistically significant effect. The implications are that stability can minimize credit risk, careful management and transparency in profit allocation can reduce agency conflicts, and the level of managerial ownership does not necessarily exert a consistent influence on dividend policy. The study highlights the importance of maintaining strong investment prospects, implementing effective corporarate governance, and making strategic financial decision to support consistent and sustainable dividend distributions.